2015
DOI: 10.1038/srep10881
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Reduce Toxicities and to Improve Bioavailabilities of Platinum-Containing Anti-Cancer Nanodrugs

Abstract: Platinum (Pt) drugs are the most potent and commonly used anti-cancer chemotherapeutics. Nanoformulation of Pt drugs has the potential to improve the delivery to tumors and reduce toxic side effects. A major challenge for translating nanodrugs to clinical settings is their rapid clearance by the reticuloendothelial system (RES), hence increasing toxicities on off-target organs and reducing efficacy. We are reporting that an FDA approved parenteral nutrition source, Intralipid 20%, can help this problem. A dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…In particular, the rapid clearance of these nanodrugs by the cells of the reticuloendothelial system (RES)/mononuclear phagocyte system (MPS), especially liver and spleen, can lead to increased toxicity to the off-target organs and reduced therapeutic efficacy. However, a recent publication suggested that such off-target effects can be reduced by Intralipid 20 % (a FDA-approved fat emulsion used as parenteral nutrition source), which could decrease the toxicities in liver and spleen and increase the bioavailability of dichloro ( 1, 2 -diaminocyclohexane) platinum (II)-loaded and hyaluronic acid polymer-coated nanoparticle (DACHPt/HANP) by possibly inhibiting peritoneal clearance and impairing the phagocytic activity of Kupffer cells [147]. Whether such reduced off target effects can also be observed in liposomal based drug delivery system is worthwhile further investigating.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the rapid clearance of these nanodrugs by the cells of the reticuloendothelial system (RES)/mononuclear phagocyte system (MPS), especially liver and spleen, can lead to increased toxicity to the off-target organs and reduced therapeutic efficacy. However, a recent publication suggested that such off-target effects can be reduced by Intralipid 20 % (a FDA-approved fat emulsion used as parenteral nutrition source), which could decrease the toxicities in liver and spleen and increase the bioavailability of dichloro ( 1, 2 -diaminocyclohexane) platinum (II)-loaded and hyaluronic acid polymer-coated nanoparticle (DACHPt/HANP) by possibly inhibiting peritoneal clearance and impairing the phagocytic activity of Kupffer cells [147]. Whether such reduced off target effects can also be observed in liposomal based drug delivery system is worthwhile further investigating.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, intralipid decreased platinum containing anti-cancer drugs accumulation in the liver, spleen, and kidney. The authors stated that the mechanism was through decreasing reticulo-endothelial system (RES) uptake and then increasing the bioavailability of the anti-cancer drug [19] . In recent years, the investigators also evaluated the mechanisms of applying intralipid in treating unexplained recurrent spontaneous abortion.…”
Section: Other New Applications Of Intralipidsmentioning
confidence: 99%
“…Incorporation of polymer which is safe as well as easily biodegradable could assist to reduce the side effects of the nanoparticles based anticancer formulation i.e. use of hyaluronan in platinum nanoparticulate based anticancer drug [46].…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%